Sign Language Training for Civil Servants at the Palangka Raya Civil Registration Office to Support Inclusive Services for Deaf Citizens - Maulida Kusumawardhani, Nazwa; Agusti, Revalina; Selvia, Fitriana (Sasambo: Jurnal Abdimas (Journal of Community Service), 2025)
Inclusive civil registration services for deaf persons are a critical prerequisite for equitable public service delivery and for advancing SDG 10 and SDG 16. At the Civil Registration Office (Disdukcapil) of Palangka Raya, physical accessibility has begun to receive attention, but staff capacity to communicate with deaf citizens remains limited and relies largely on written notes or family members as intermediaries. This community service programme aimed to strengthen the capacity of civil servants to provide more inclusive services through a short training on basic sign language and disability awareness. The intervention was implemented as a face-to-face workshop with three stages: preparation (needs mapping and development of a concise training module), implementation (presentation of disability-related regulations and inclusive service principles, introduction to SIBI and BISINDO manual alphabets, and role-plays simulating interactions at the service counter), and simple evaluation using written reflection sheets and group discussion. The findings indicate increased awareness among participants of deaf citizens’ communication rights, a more critical view of previous communication strategies, and greater confidence to initiate interaction using a combination of sign language, writing, and gestures. Participants also began to recognise the need for institutional support, such as Standard Operating Procedures and follow-up training, so that inclusive practice does not depend solely on individual goodwill. Although short in duration and limited to basic competencies, the programme illustrates how sign language training can serve as a practical entry point for strengthening disability-inclusive civil registration services for deaf citizens.